Quality of life’s Policeman Development by Using Sufficiency Economy Based - Phuyiamchit, Lt. Col. Dr.Narong (Journal for Developing the Social and Community, 2018)
Sufficiency economy is important to both individuals and society because daily life requires moderation, reason and a good immune system. This principle is applied in everyday life. Self-reliance when self-reliant community and society will be stable, sustainable development. Ready to cope with any change that may occur at any time. It can be seen that sufficiency economy is close to being able to be implemented. And consequently, the benefits of continuous serious practice. Applying sufficiency economy as a base for everyday use. It discusses the basic necessity theory and modern because it is based on the present self-sufficiency principle. So the police put sufficiency economy as the basis for improving the quality of life. Follow the way of daily life, it is the development and quality of life. In current economic and environmental conditions. Can be used to improve the wellbeing of the police. Using sufficiency economy as a base build a good understanding of the correct lifestyle. Know enough life planning, analysis, and judgment. By reason is a place to know, diligent, honest, patient, economical and not extravagant. In addition, no matter what you do. Need more knowledge to enhance your skills. The teachings of Buddhism should strictly follow. To guide and develop the quality of life of the police.